Riding the wave into wellbeing: A qualitative evaluation of surf therapy for individuals living with acquired brain injury - Gibbs, Katie; Wilkie, Lowri; Jarman, Jack; Barker-Smith, Abigail; Kemp, Andrew H.; Fisher, Zoe (PloS one, 2022)
Nature has long demonstrated the capacity to facilitate wellbeing. Interventions involving the natural environment such as surf therapy, are increasingly being used to facilitate aspects of wellbeing in clinical populations. However, explorations of how nature-based interventions such as surf therapy may be used to promote wellbeing in the context of neurorehabilitation are missing from the peer-reviewed literature. Here we characterize the experience of a five-week surfing intervention involving fifteen adults living with the psycho-social and cognitive sequelae of acquired brain injury. Insights were analysed using reflexive thematic analysis, which highlighted the importance of seven overarching themes, including: 1) Connection to Nature, 2) Facilitating Trust and Safety, 3) Managing and Accepting Difficult Emotions, 4) Facilitating Positive Emotion, Meaning and Purpose, 5) Building Community through Social Connection, and 6) Positive Change. Barriers and opportunities (theme 7) were also identified as components on which clinical services may be improved. We present a theoretical model for the benefits of surf therapy in people living with acquired brain injury (ABI) based on these themes and reflections on findings from the wider literature. Findings emphasise the importance of leveraging community partnerships to augment the holistic model of neurorehabilitation and potential implications for service redesign are discussed, focusing on recent developments in wellbeing science.